2017
DOI: 10.31937/sk.v9i1.572
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Algoritma Stemming Nazief-Adriani Terhadap Kinerja Algoritma Winnowing Untuk Mendeteksi Plagiarisme Bahasa Indonesia

Abstract: Winnowing algorithm is one among many algorithms for detecting document similarity and plagiarism. Some studies show that Winnowing algorithm performs quite well. One form of plagiarism is paraphrase plagiarism. Paraphrase plagiarism can be done by changing sentence structure, changing vocabulary, and adding or changing affixes. Based on some of our previous experiments, detecting document resemblances can be enhanced by changing the words containing affixes to their basic words. In computer science, this tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…Dalam penelitian ini memakai metode fingerprinting dan algoritma yang dipakai pada metode ini merupakan algoritma Winnowing. Penggunaan algoritma Winnowing untuk menaikkan efisiensi menurut proses perbandingan dokumen serta hasil menurut algoritma winnowing merupakan nilai fingerprinting [2]. Nilai fingerprinting yang didapatkan menurut algoritma winnowing dipakai untuk mengukur persentase kemiripan antara dokumen skripsi menggunakan dokumen skripsi lainnya menggunakan pengukuran dice similarity distance serta chebyshev distance.…”
Section: Pendahuluanunclassified
“…Dalam penelitian ini memakai metode fingerprinting dan algoritma yang dipakai pada metode ini merupakan algoritma Winnowing. Penggunaan algoritma Winnowing untuk menaikkan efisiensi menurut proses perbandingan dokumen serta hasil menurut algoritma winnowing merupakan nilai fingerprinting [2]. Nilai fingerprinting yang didapatkan menurut algoritma winnowing dipakai untuk mengukur persentase kemiripan antara dokumen skripsi menggunakan dokumen skripsi lainnya menggunakan pengukuran dice similarity distance serta chebyshev distance.…”
Section: Pendahuluanunclassified
“…The previous research [21], [11] which carried out the application of the stemmer algorithm S_P and S_NA on the winnowing algorithm resulted in the performance of the winnowing algorithm faster in plagiarism detection, but it is not yet known that the stemmer algorithm has a better influence on the winnowing algorithm in measuring the similarity value and the speed of the process.…”
Section: B Related Workmentioning
confidence: 99%
“…Previous research that applied stemming Porters to the Winnowing algorithm was carried out by [11], his research showed that the Porter stemmer algorithm helped speed up the winnowing algorithm in determining the value of fingerprints of a text. Furthermore, the effect of Naziefadriani's stemming algorithm on the performance of the Winnowing algorithm to detect Indonesian language plagiarism by [12], his research resulted in a stemming process in the Winnowing algorithm which tends to reduce the similarity level but speeds up processing time by approximately 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Algoritma yang dibuat oleh Bobby Nazief dan Mirna Adriani memiliki tahapan sebagai berikut. [2] 1. Cari kata yang akan distem dalam kamus.…”
Section: Algoritma Stemming Nazief and Adrianiunclassified